Compressive strength of recycled aggregate concrete with various percentage of recycled aggregate - Adnan, Suraya Hani (2007)
Compressive strength is the basic mechanical properties and one of the indicators to determine the performance of a concrete. In this paper, the effects of various percentages (0%, 25%, 50%, 75%, 100%) of Recycled Aggregate (RA) on compressive strength of Recycled Aggregate Concrete (RAC) were investigated. RA is used to replace natural aggregate (NA) as coarse aggregate in concrete mixes. This research also covered RAC mixtures at different water-cement ratio (0.4, 0.5, 0.6). It was found that RAC had lower compressive strength compared to Natural Aggregate Concrete (NAC). At the age of 28 days, RAC with water-cement ratio 0.4 had the highest strength.